Effect of a leukotriene receptor antagonist pranlukast hydrate, on airway inflammation airway hyperresponsiveness in patients with moderate to severe asthma - Kiyoko Wada (Allergology International, 2000)
Asthma is characterized by chronic airway inflammation and the recruitment of inflammatory cells, typically eosinophils and lymphocytes, into the airway. Although several chemical mediators are released during the inflammatory process of asthma, evidence strongly suggests that the cysteinyl leukotrienes (LT), LTC4, LTD4, and LTE4, play key roles in asthma. The short-term clinical efficacy of an LT receptor antagonist, pranlukast hydrate, in symptomatic patients with asthma who had already been treated with moderate to high doses of inhaled corticosteroids was therefore investigated. Treatment with pranlukast hydrate for 4 weeks significantly improved respiratory function and decreased asthma symptoms, the rescue use of inhaled β2-agonists, the number of peripheral blood eosinophils and serum levels of eosinophil cationic protein. Furthermore, airway inflammation, as evaluated by the percentage of eosinophils in induced sputum and airway responsiveness to histamine, decreased significantly after treatment. There were no significant changes in these parameters in control patients with asthma whose treatment was not changed over 4 weeks. These preliminary results suggest that pranlukast hydrate, an LT receptor antagonist, is an effective agent in the management of asthma in combination with moderate to high doses of inhaled corticosteroids.